A mathematical model of crevice corrosion for buried pipeline with disbonded coatings under cathodic protection. (May 2016) - Wang, Wenhe; Shen, Kuiling; Yi, Jun; Wang, Qingsheng
Abstract: Crevice corrosion occurs in a holiday and disbonded region between coating and pipeline steel. Cathodic protection (CP) is generally recognized as the most effective method for corrosion prevention of pipeline, but its effectiveness may be reduced at defects in a disbonded coating. It is difficult to measure and probe corrosion parameters accurately based on experimental work. Therefore, a mathematical model is necessary to identify the phenomena and mechanisms that contribute to the crevice corrosion process. In this work, a mathematical model was developed to determine the evolution of chemical and electrochemical transient processes of crevice corrosion in NaCl dilute solution, and the effect of cathodic protection and crevice width on corrosion of 20# steel pipeline with disbonded coatings. Results have demonstrated that the extent of crevice corrosion depends on the crevice geometry and could be influenced by the increase of crevice depth and decrease of its width. The oxygen concentrations drop significantly inside a crevice whether CP is applied or not and whether crevice width decreased or not. The pH values and conductivity of crevice solution increase with the time. The research provides a theoretical foundation for cathodic protection of pipelines and establishes an effective corrosion model which can identify the phenomena and mechanisms of the crevice corrosion process. This work could be used to help mitigate the corrosion failure of pipelines to prevent catastrophic accidents in oil, gas and chemical process industries. Highlights: A mathematical model is developed to identify the corrosion phenomena. Extent of crevice corrosion depends on the crevice geometry. The model matches the experimental results very well. The research provides a theoretical foundation for cathodic protection of pipelines.